PENINGKATAN KETUNTASAN HASIL BELAJAR DAN AKTIVITAS BELAJA SISWA MENGGUNAKAN MODEL PEMBELAJARAN TIPEJIGSAW DI SMP AL-HIDAYAH BALUNG - Pratikno, Agus; Hariyadi, Slamet; Khusnah, Laila (Pendidikan Biologi,Universitas Islam Jember, 2014)
Education is a conscious and deliberate effort to create an atmosphere of learning and the learning process so that learners are actively developing the potential for him to have the spiritual strength of religious, self-control, personality, intelligence, good values, and skill that need him, society, nation and state ( Ministry of Education, 2003: 6). The formulation of this problem are: 1) Is the Jigsaw model can improve the learning activity of students in class VII student studying biology junior year Alhidayah Karangduren Lessons Balung 2011/2012?. 2) Is the Jigsaw model of learning can improve learning outcomes completeness biology class VII SMP Alhidayah karangduren Balung Academic Year 2011/2012?. This study aims to: 1) Assess the effectiveness of Jigsaw model of learning in improving student learning outcomes completeness class VII SMP Al-Hidayah Karangduren Lessons Balung year 2011/2012. 2) Assess the effectiveness of instructional models up grade Jigsaw in class VII student learning activities SMP Al-Hidayah Karangduren Lessons Balung year 2011/2012. By using the Jigsaw cooperative learning model, showed high learning outcomes, can be seen from the results of your analysis test on the subject of the previous gain (62.85%) compared to the type of cooperative learning jigsaw, the first to reach the cycle (71, 42%). And the cycle is continued on to the second cycle reached (91.42%) of students scoring above the minimum completeness criteria. Kata kunci (key word) aktivitas, hasil belajar, jigsaw